Mechanical properties of MIRHA-fly ash geopolymer concrete - Bayuaji, R. (Trans Tech Publications Ltd, 2015)
This paper provides a report about the results of an investigation carried out to understand the effect of Microwave Incinerated Rice Husk Ash (MIRHA) on the mechanical properties of fly ash geopolymer concrete to access the concrete performance development. Fly ash (350kg/m3) and MIRHA (0, 3, and 7) were used as the source materials to replace cement, NaOH and Na2SiO3 solutions used as the alkaline liquids for the medium of polymeric reaction. In addition, sugar was used as retarder, as well as three different types of curing regime (ambient, external exposure or oven curing regime). The concrete mixing procedure was adjusted to obtain the proper homogeneity of dry materials and wet ones. In this project, a number of mechanical tests have been conducted including the pull-out test, compressive strength test, flexural strength test, and modulus of elasticity test. It was then observed that the performance of mechanical properties of MIRHA-fly ash geopolymer concrete improved with the use of oven curing as the curing regime for the concrete samples. Â© (2015) Trans Tech Publications, Switzerland.